Modified lithium-rich manganese-based material as well as preparation method and application thereof

Through the modification method of doping tungsten and sulfur elements, the shortcomings of the existing lithium-rich manganese-based positive electrode materials in the first discharge specific capacity and cycling performance are solved, especially in high-temperature environments, which significantly improve the battery performance.

CN119419241APending Publication Date: 2025-02-11GEM WUXI ENERGY MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411538696.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials have limited improvements in the first discharge specific capacity and cycling performance, especially in high temperature environments.

Method used

By mixing the precursor, tungsten source and lithium source, a calcined material is obtained, and then mixed with sulfur element additive and organic solvent to stir and sinter to form a modified lithium-rich manganese-based material. This method increases the distance between the lithium layer by doping tungsten and sulfur elements, forming a stable Li-rich layered structure, inhibits structure collapse, and improves circulation stability.

Benefits of technology

It significantly improves the battery's first discharge specific capacity and cycle stability, and performs better especially under high temperature conditions, extending the battery's service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112243060000081
    Figure BDA0005112243060000081
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and particularly relates to a modified lithium-rich manganese-based material and a preparation method and application thereof. The preparation method of the modified lithium-rich manganese-based material comprises the following steps: 1) mixing a precursor, a tungsten source and a lithium source, and calcining to obtain a calcined material; and 2) mixing and stirring the calcined material obtained in the step 1), a sulfur element additive and an organic solvent, and sintering to obtain the modified lithium-rich manganese-based material. Through mutual cooperation of the steps, when the obtained modified lithium-rich manganese-based material is applied to a battery, the first discharge specific capacity and the cycle performance of the battery can be remarkably improved, and particularly, the first discharge specific capacity and the cycle performance of the battery under a high-temperature condition are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a modified lithium-rich manganese-based material and a preparation method and application thereof. Background Art

[0002] The emergence of new lithium-ion power batteries has solved the problem of insufficient traditional energy to a certain extent. Lithium-rich manganese oxide (LRMO) has become one of the options for the next generation of lithium-ion battery cathode materials due to its low cost, high energy density and excellent thermal stability.

[0003] However, the development of lithium-rich manganese-based positive electrode materials is seriously hindered due to the fact that lithium-rich manganese-based positive electrode materials are prone to capacitance attenuation, poor rate performance, voltage attenuation, etc. Therefore, there is an urgent need to modify lithium-rich positive electrode materials to meet the current growing demand for power batteries. At present, element doping, surface coating, and liquid or gas phase post-treatment have a certain effect on improving the electrochemical performance of lithium-rich manganese-based positive electrode materials, but different modification methods produce different improvement effects. The lithium-rich manganese-based positive electrode materials obtained by the existing modification methods still have limited improvements in the first discharge specific capacity and cycle performance, especially the first discharge specific capacity and cycle performance under high temperature environment still need to be improved. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of existing lithium-rich manganese-based positive electrode materials that still have limited improvement in initial discharge specific capacity and cycle performance, thereby providing a modified lithium-rich manganese-based material and its preparation method and application.

[0005] The present invention provides a method for preparing a modified lithium-rich manganese-based material, comprising the following steps:

[0006] 1) mixing a precursor, a tungsten source and a lithium source, and calcining to obtain a calcined material;

[0007] 2) The calcined material obtained in step 1), the sulfur additive and the organic solvent are mixed, stirred and sintered to obtain the modified lithium-rich manganese-based material.

[0008] Preferably, the tungsten source in step 1) is selected from at least one of tungsten trioxide, ammonium metatungstate, sodium metatungstate, tungsten chloride, lithium tungstate, and tungsten disulfide;

[0009] The lithium source is selected from at least one of lithium carbonate and lithium hydroxide.

[0010] Preferably, the calcination in step 1) includes a first calcination and a second calcination;

[0011] The first calcination temperature is 450-550°C; the first calcination time is 4h-8h;

[0012] The second calcination temperature is 800-900°C, and the second calcination time is 10-20h;

[0013] The calcination is performed in an oxygen-containing atmosphere.

[0014] Optionally, the calcination is carried out under an air atmosphere;

[0015] Optionally, after the calcination step, the steps of cooling, crushing and screening are also included.

[0016] Optionally, the mixing in step 1) is carried out under stirring, with a stirring speed of 300-1500 rpm and a stirring time of 10-120 min.

[0017] Preferably, the ratio of the total molar amount of the metal element in the precursor to the molar amount of the tungsten element in the tungsten source in step 1) is 1:(0.002-0.004);

[0018] The sum of the total molar amount of the metal elements in the precursor and the molar amount of the tungsten element in the tungsten source is recorded as a, and the molar amount of the lithium element in the lithium source is recorded as b, and b:a is (1.35-1.6):1.

[0019] Preferably, the chemical formula of the precursor in step 1) is Mn x Ni y (OH)2, and 0.3≤x≤0.8, 0.1≤y≤0.5, x+y=1;

[0020] The average particle size of the precursor is 7.8-8.2 μm.

[0021] Preferably, the sulfur additive in step 2) is at least one selected from sodium thiosulfate, sodium sulfate, diethyl sulfite, and lithium sulfide;

[0022] The organic solvent is selected from at least one of ethanol, propanol, isopropanol and n-butanol.

[0023] Preferably, the mass ratio of the calcined material, the sulfur additive and the organic solvent is (1-25): (0.01-0.1): (10-25).

[0024] Preferably, the sintering temperature in step 2) is 400-700° C., and the sintering time is 5-10 h;

[0025] Optionally, the mixing and stirring step in step 2) further includes a drying step.

[0026] Optionally, the mixing and stirring speed in step 2) is 400-600 rpm, and the mixing and stirring time is 10-30 min;

[0027] The drying temperature is 80-110° C., and the drying time is 5-12 hours.

[0028] The present invention provides a modified lithium-rich manganese-based material, which is prepared by the above-mentioned method for preparing the modified lithium-rich manganese-based material.

[0029] The present invention also provides an application of the modified lithium-rich manganese-based material described above in a lithium-ion battery.

[0030] The technical solution of the present invention has the following advantages:

[0031] The preparation method of the modified lithium-rich manganese-based material provided by the present invention comprises the following steps: 1) mixing a precursor, a tungsten source and a lithium source, calcining to obtain a calcined material; 2) mixing and stirring the calcined material obtained in step 1), a sulfur element additive and an organic solvent, and sintering to obtain the modified lithium-rich manganese-based material. The present invention not only increases the distance between lithium layers by doping W elements with a slightly larger radius, but also reduces the space barrier between lithium layers, thereby increasing the transmission rate of lithium ions, forming a column effect to stabilize the Li-rich layered structure, inhibiting the collapse of the structure during the cycle, and improving the cycle stability. Furthermore, by coating the calcined material with sulfur, firstly, the S element forms a doping in the shallow surface layer of the calcined material, and forms a double element doping with the W element in the shallow surface layer of the material, and the two act synergistically to enhance the structural stability of the positive electrode material, and the relatively inert S element will not affect the ion transfer rate of the material, reducing the impact of high temperature on the positive electrode material; secondly, S reacts with the lithium in the cathode and the electrolyte in the electrolyte during the charge and discharge process, and forms a thin and dense cathode-electrolyte interface (CEI) layer composed of RSO3Li, R2SO3 and Li2SO3 on the particle surface. In addition, due to the electron-rich nature of S=O, the S=O group can also inhibit the reactivity of PF5 generated during the cycle, and the S=O group acts as a weak base site to inhibit the generation of HF, thereby enhancing the cycle stability at high temperature. The modified lithium-rich manganese-based material obtained by the present invention cooperates with each other through specific steps, and can be applied to the battery to significantly improve the first discharge specific capacity and cycle stability of the battery, especially significantly improve the first discharge specific capacity and cycle stability of the battery under high temperature conditions. DETAILED DESCRIPTION

[0032] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0033] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0034] Example 1

[0035] This embodiment provides a method for preparing a modified lithium-rich manganese-based material, comprising the following steps:

[0036] 1) 62.6 g lithium carbonate and 100 g Mn 0.65 Ni 0.35 (OH)2 precursor (average particle size of 8 μm) and 0.62 g of tungsten trioxide were stirred and mixed at 700 rpm for 20 min, calcined at 450 °C for 5 h in air atmosphere, then heated to 850 °C for 10 h, then cooled to room temperature, crushed, and sieved to obtain a calcined material;

[0037] 2) 20 g of the calcined material obtained in step 1) and 0.062 g of sodium sulfate were added to 20 g of ethanol solution, mixed and stirred at 500 rpm for 20 min at room temperature, then vacuum dried at 80° C. for 5 h, and then sintered at 600° C. for 8 h to obtain the modified lithium-rich manganese-based material.

[0038] Example 2

[0039] This embodiment provides a method for preparing a modified lithium-rich manganese-based material, comprising the following steps:

[0040] 1) 62.6 g lithium carbonate and 100 g Mn 0.65 Ni 0.35 (OH)2 precursor (average particle size of 8 μm) and 0.62 g of tungsten trioxide were stirred and mixed at 300 rpm for 30 min, calcined at 550 ° C for 6 h in air atmosphere, then heated to 900 ° C for 13 h, then cooled to room temperature, crushed, and sieved to obtain a calcined material;

[0041] 2) adding 25 g of the calcined material obtained in step 1) and 0.3 g of sodium sulfate to 25 g of ethanol solution, stirring at 400 rpm for 30 min at room temperature, then vacuum drying at 110° C. for 8 h, and then sintering at 400° C. for 10 h to obtain the modified lithium-rich manganese-based material.

[0042] Example 3

[0043] This embodiment provides a method for preparing a modified lithium-rich manganese-based material, comprising the following steps:

[0044] 1) 62.6 g lithium carbonate and 100 g Mn 0.65 Ni 0.35(OH)2 precursor (average particle size of 8 μm) and 0.62 g of tungsten trioxide were stirred and mixed at 1500 rpm for 10 min, calcined at 500 °C for 4 h in an air atmosphere, then heated to 800 °C for 20 h, then cooled to room temperature, crushed, and sieved to obtain a calcined material;

[0045] 2) 20 g of the calcined material obtained in step 1) and 0.062 g of sodium sulfate were added to 20 g of ethanol solution, mixed and stirred at 600 rpm for 10 min at room temperature, then vacuum dried at 90° C. for 6 h, and then sintered at 700° C. for 5 h to obtain the modified lithium-rich manganese-based material.

[0046] Example 4

[0047] This embodiment provides a method for preparing a modified lithium-rich manganese-based material, comprising the following steps:

[0048] 1) 62.6 g lithium carbonate and 100 g Mn 0.65 Ni 0.35 (OH)2 precursor (average particle size of 8 μm) and 0.62 g of tungsten trioxide were stirred and mixed at 700 rpm for 20 min, calcined at 450 °C for 5 h in air atmosphere, then heated to 850 °C for 10 h, then cooled to room temperature, crushed, and sieved to obtain a calcined material;

[0049] 2) 20 g of the calcined material obtained in step 1) and 0.062 g of sodium thiosulfate were added to 15 g of propanol solution, mixed and stirred at 500 rpm for 20 min at room temperature, then vacuum dried at 80° C. for 5 h, and then sintered at 600° C. for 8 h to obtain the modified lithium-rich manganese-based material.

[0050] Example 5

[0051] This embodiment provides a method for preparing a modified lithium-rich manganese-based material, comprising the following steps:

[0052] 1) 62.6 g lithium carbonate and 100 g Mn 0.65 Ni 0.35 (OH)2 precursor (average particle size of 8 μm) and 0.62 g of tungsten trioxide were stirred and mixed at 700 rpm for 20 min, calcined at 450 °C for 5 h in air atmosphere, then heated to 850 °C for 10 h, then cooled to room temperature, crushed, and sieved to obtain a calcined material;

[0053] 2) 20 g of the calcined material obtained in step 1) and 0.062 g of diethyl sulfite were added to 20 g of ethanol solution, mixed and stirred at 500 rpm for 20 min at room temperature, then vacuum dried at 80° C. for 5 h, and then sintered at 600° C. for 8 h to obtain the modified lithium-rich manganese-based material.

[0054] Comparative Example 1

[0055] This comparative example provides a method for preparing a modified lithium-rich manganese-based material, comprising the following steps:

[0056] 1) 62.6 g lithium carbonate and 100 g Mn 0.65 Ni 0.35 The (OH)2 precursor (average particle size of 8 μm) was stirred and mixed at 700 rpm for 20 min, calcined at 450°C for 5 h in an air atmosphere, then heated to 850°C for 10 h, then cooled to room temperature, crushed, and sieved to obtain a calcined material;

[0057] 2) adding 20 g of the calcined material obtained in step 1) into 20 g of ethanol solution, stirring at 500 rpm for 20 min at room temperature, then vacuum drying at 80° C. for 5 h, and then sintering at 600° C. for 8 h to obtain the modified lithium-rich manganese-based material.

[0058] Comparative Example 2

[0059] This comparative example provides a method for preparing a modified lithium-rich manganese-based material, comprising the following steps:

[0060] 1) 62.6 g lithium carbonate and 100 g Mn 0.65 Ni 0.35 (OH)2 precursor (average particle size of 8 μm) and 0.62 g of tungsten trioxide were stirred and mixed at 700 rpm for 20 min, calcined at 450 °C for 5 h in air atmosphere, then heated to 850 °C for 10 h, then cooled to room temperature, crushed, and sieved to obtain a calcined material;

[0061] 2) adding 20 g of the calcined material obtained in step 1) into 20 g of ethanol solution, stirring at 500 rpm for 20 min at room temperature, then vacuum drying at 80° C. for 5 h, and then sintering at 600° C. for 8 h to obtain the modified lithium-rich manganese-based material.

[0062] Comparative Example 3

[0063] This comparative example provides a method for preparing a modified lithium-rich manganese-based material, comprising the following steps:

[0064] 1) 62.6 g lithium carbonate and 100 g Mn 0.65 Ni 0.35 The (OH)2 precursor (average particle size of 8 μm) was stirred and mixed at 700 rpm for 20 min, calcined at 450°C for 5 h in an air atmosphere, then heated to 850°C for 10 h, then cooled to room temperature, crushed, and sieved to obtain a calcined material;

[0065] 2) 20 g of the calcined material obtained in step 1) and 0.062 g of sodium sulfate were added to 20 g of ethanol solution, mixed and stirred at 500 rpm for 20 min at room temperature, then vacuum dried at 80° C. for 5 h, and then sintered at 600° C. for 8 h to obtain the modified lithium-rich manganese-based material.

[0066] Test Case

[0067] The modified lithium-rich manganese-based materials in Examples 1-5 and Comparative Examples 1-3 were used as the main materials to prepare button batteries, respectively. The main materials, polyvinylidene fluoride (PVDF), acetylene black, and N-methylpyrrolidone were slurried in a mass ratio of 80:10:10:100 and coated on aluminum foil, and dried to obtain positive electrode sheets (compacted surface density 5.0 mg / cm 2 ); using metallic lithium as the negative electrode, glass fiber as the separator, and 1 mol / L LiPF6 ethylene carbonate (EC) / dimethyl carbonate (DMC) solution as the electrolyte (the volume ratio of EC to DMC is 1:1), in an argon atmosphere of a glove box, the positive electrode, the negative electrode, the electrolyte, the separator, the gasket and the spring are placed in a button battery shell to assemble a button battery.

[0068] The prepared button batteries were placed in the Blue Electric test system for electrical performance testing. The test conditions were: charge and discharge voltage range 2.0V-4.8V, test temperature 25°C, firstly, the battery's initial charge and discharge performance at 25°C was tested with a 0.1C / 0.1C cycle for 1 week, and then the battery's cycle performance at 25°C was tested with a 1C / 1C cycle for 50 weeks. The test results are shown in Table 1.

[0069] Newly prepared button cells were placed in the Blue Electric test system for electrical performance testing. The test conditions were: charge and discharge voltage range 2.0V-4.8V, test temperature 60°C, and the battery was first cycled at 0.1C / 0.1C for one week to test the first charge and discharge performance at 60°C. The battery was then cycled at 1C / 1C for 50 weeks to test the cycle performance at 60°C. The test results are shown in Table 1.

[0070] Table 1

[0071]

[0072] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a modified lithium-rich manganese-based material, characterized in that: The following steps are involved: 1) mixing a precursor, a tungsten source and a lithium source, and calcining to obtain a calcined material; 2) The calcined material obtained in step 1), the sulfur additive and the organic solvent are mixed, stirred and sintered to obtain the modified lithium-rich manganese-based material.

2. The method for preparing the modified lithium-rich manganese-based material according to claim 1, characterized in that: The tungsten source in step 1) is selected from at least one of tungsten trioxide, ammonium metatungstate, sodium metatungstate, tungsten chloride, lithium tungstate, and tungsten disulfide; The lithium source is selected from at least one of lithium carbonate and lithium hydroxide.

3. The method for preparing the modified lithium-rich manganese-based material according to claim 1 or 2, characterized in that: The calcination in step 1) includes a first calcination and a second calcination; The first calcination temperature is 450-550°C; the first calcination time is 4h-8h; The second calcination temperature is 800-900°C, and the second calcination time is 10-20h; The calcination is performed in an oxygen-containing atmosphere.

4. The method for preparing the modified lithium-rich manganese-based material according to any one of claims 1 to 3, characterized in that: The ratio of the total molar amount of the metal element in the precursor in step 1) to the molar amount of the tungsten element in the tungsten source is 1:(0.002-0.004); The sum of the total molar amount of the metal elements in the precursor and the molar amount of the tungsten element in the tungsten source is recorded as a, and the molar amount of the lithium element in the lithium source is recorded as b, and b:a is (1.35-1.6):

1.

5. The method for preparing the modified lithium-rich manganese-based material according to any one of claims 1 to 4, characterized in that: The chemical formula of the precursor in step 1) is Mn x Ni y (OH)2, and 0.3≤x≤0.8, 0.1≤y≤0.5, x+y=1; The average particle size of the precursor is 7.8-8.2 μm.

6. The method for preparing the modified lithium-rich manganese-based material according to any one of claims 1 to 5, characterized in that: The sulfur additive in step 2) is selected from at least one of sodium thiosulfate, sodium sulfate, diethyl sulfite, and lithium sulfide; The organic solvent is selected from at least one of ethanol, propanol, isopropanol and n-butanol.

7. The method for preparing the modified lithium-rich manganese-based material according to claim 6, characterized in that: The mass ratio of the calcined material, the sulfur element additive and the organic solvent is (1-25): (0.01-0.1): (10-25).

8. The method for preparing the modified lithium-rich manganese-based material according to claim 6 or 7, characterized in that: The sintering temperature in step 2) is 400-700°C and the sintering time is 5-10h; Optionally, the mixing and stirring step in step 2) further includes a drying step.

9. A modified lithium-rich manganese-based material, characterized in that: The modified lithium-rich manganese-based material is prepared by the preparation method of any one of claims 1 to 8.

10. Use of the modified lithium-rich manganese-based material according to claim 9 in lithium-ion batteries.

Citation Information

Cited By

  • Lithium-rich manganese-based positive electrode material with gradient oxygen skeleton stable structure and preparation method of lithium-rich manganese-based positive electrode material

    CN122511874A